Electronic Tap-changer for Distribution Transformers - Faiz, Jawad; Siahkolah, Behzad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This reference collects all relevant aspects electronic tap-changer and presents them in a comprehensive and orderly manner. It explains logically and systematically the design and optimization of a full electronic tap-changer for distribution transformers. The book provides a fully new insight to all possible structures of power section design and categorizes them comprehensively, including cost factors of the design. In the control section design, the authors review mechanical tap-changer control systems and they present the modeling of a full electronic tap-changer as well as a closed-loop control of the full-electronic tap-changer. The book is written for electrical engineers in industry and academia but should be useful also to postgraduate students of electrical engineering.
Transformer Tap-changer: Past and Present -- Designing Taps windings structure and switches configuration in a full-electronic tap-changer -- Bi-directional semiconductor switches in full-electronic tap-changer -- Tap-changer controller design: Voltage regulation -- Tap-changer as a power demand tools -- Practical Realization and experimental results -- Conclusions and recommendations.
Keywords: Engineering; Production of electric energy or power; Engineering; Power Electronics, Electrical Machines and Networks